2015
DOI: 10.1007/s00432-015-2066-3
|View full text |Cite
|
Sign up to set email alerts
|

A photodynamic therapy combined with topical 5-aminolevulinic acid and systemic hematoporphyrin derivative is more efficient but less phototoxic for cancer

Abstract: The combined PDT not only shows high cure rate for skin cancers but also decreases the dose of the pro-toxic HPD and significantly shortens the photosensitive period, from which the patients are able to benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 21 publications
1
33
0
Order By: Relevance
“…[30][31][32][33] Photodynamic therapy using porphyrin derivatives, however, often results in prolonged systemic side effects, especially if the photosensitizing agent is injected. 34 This led to development of second-and third-generation photosensitizers with more specificity toward tumor cells while sparing normal cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[30][31][32][33] Photodynamic therapy using porphyrin derivatives, however, often results in prolonged systemic side effects, especially if the photosensitizing agent is injected. 34 This led to development of second-and third-generation photosensitizers with more specificity toward tumor cells while sparing normal cells.…”
Section: Discussionmentioning
confidence: 99%
“…51,52 Studies have shown that topical application of photosensitizing agents, such as in dermatologic applications, is also effective. 34 Fluid-filled balloons that distribute the light to the cavity walls have been studied to evenly distribute the therapeutic light throughout. 5 Recently, a few studies have also demonstrated the potential application of interstitial PDT applied via laser fibers for intra-tumor light delivery in non-resectable and recurrent glioblastomas.…”
Section: Discussionmentioning
confidence: 99%
“…However, similar approaches have been poorly explored in the field of PDT. Few investigations have been published involving the combination of two PSs targeting different subcellular compartments, but the results are very promising [38][39][40][41][42][43][44][45][46]. Interestingly, most of these studies have involved the use of porphyrinic compounds.…”
Section: Combination Of Tmpyp With Other Photosensitizersmentioning
confidence: 99%
“…Moreover, topical usage of antibiotic has many potential advantages over systematic use. At present, the benefits of topical antibiotic prophylaxis and treatment with various agents have been documented for multiple surgical disciplines, including ophthalmic, orthopaedic, neurological, urological and general surgeries …”
Section: Introductionmentioning
confidence: 99%